The effect of cupric ions on the corrosion behaviour of brass CuZn42 in an acid environment - Avramović Zoran; Antonijević Milan; Avramović Ljiljana; Božić Dragana; Trifunović Vanja (Mining and Metallurgy Engineering Bor, 2025)
This paper presents the results of research on the corrosion behavior of brass CuZn42 in an acidic environment, in the presence of copper ions. Based on the recorded anodic polarization curves, it was concluded that as the concentration of copper ions in the tested solution increases, the corrosion current densities also increase. This is reflected in the occurrence of the decinking process of brass, during which zinc is deposited on its surface, while the remaining porous copper stays within the brass mass.